2020
DOI: 10.18203/2320-6012.ijrms20203464
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of clinical profile of acute ischemic stroke in a tertiary care hospital of North India

Abstract: Background: Owing to the recent demographic shifts and negative lifestyle changes, stroke is one of the leading causes of mortality across every income group in most of the countries. It is of the utmost importance to devolve into the clinical profile, etiology and management of patients with acute ischaemic stroke.Methods: It is a prospective case control study. Data was collected using a pre-tested pro forma meeting the objectives of the study. Patients who consented were divided into two groups and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…4 A study from Lucknow, India also revealed that male was more vulnerable for stroke with 68%. 3 Similar study from AIMS, Delhi showed male predominance with M:F ratio of 5:1. Gender distribution of acute stroke patients differs from country to country.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…4 A study from Lucknow, India also revealed that male was more vulnerable for stroke with 68%. 3 Similar study from AIMS, Delhi showed male predominance with M:F ratio of 5:1. Gender distribution of acute stroke patients differs from country to country.…”
Section: Discussionmentioning
confidence: 67%
“…4 A study from North, India found that the mean age of ischemic stroke patients was 60. 3 Stroke has been increasing in younger age groups due to unhealthy lifestyles and modernization. A study from North India revealed that the mean age of stroke patients was 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the National Health Service (NHS) showed that the percentage of stroke victims who reached the hospital within the designated time frames was 40.2% within three hours of symptom onset, 51.6% within 4.5 hours, and 59.14% within six hours; furthermore, the data from the month of August 2023 showed that the average time for ambulance patients suffering from a stroke from a 999 emergency call to hospital arrival was one hour and 31 minutes, which was a decrease of more than 17 minutes from the previous year, showing an improved trend [ 15 ]. However, there are regional variations in the percentage of ischemic stroke patients who arrive at the hospital within 4.5 hours, as a study carried out in a North Indian tertiary care hospital revealed that 36.17% of acute ischemic stroke patients arrived within the 4.5-hour window and were deemed eligible for thrombolysis [ 16 ]. According to the study, 91% of acute stroke patients in Uganda presented to the emergency room after three hours, indicating a significant delay; only 9% of acute stroke patients reached the tertiary center within three hours of the onset of symptoms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%